The Relationship Between Knowledge of Dental Health Maintenance and Debris Index - Regina Amelia Muslim; Sri Hidayati; Sunomo Hadi; I.G.A Kusuma Astuti N.P (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Health is essential for overall well-being and productivity, and oral health is closely linked to general health. Issues in the mouth can affect the whole body and human quality of life. At Sanggar Alang-Alang, for the preliminary observation 10 children showed an average OHIS score of 3.2 and a Debris Index of 2.1—both in the poor category. This study aimed to examine the relationship between dental health knowledge and the Debris Index among 48 street children using a cross-sectional correlation design. Data were collected through questionnaires and oral examinations, then analyzed with the Spearman Rank test. Results showed no relationship between dental health knowledge and the Debris Index. Although most adolescents had good knowledge, their debris levels remained high. This indicates that knowledge alone is not enough to ensure good oral hygiene; proper attitudes and behaviors must also support it